2015
DOI: 10.2527/jas.2014-8718
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of factors associated with hepatic gluconeogenesis in response to acute lipopolysaccharide in dairy goat1

Abstract: Lipopolysaccharide (LPS) is a common pathogenic agent that causes many diseases and metabolic disorders. Hypoglycemia is often observed when animals are infected with LPS. To explore the influence of LPS on blood glucose and hepatic gluconeogenesis in goats, 12 goats were randomly assigned to 1 of 2 groups: the LPS-treated group (60 μg/kg BW of LPS; jugular vein injections) or the control group (saline vehicle; jugular vein injections). Blood samples were collected from jugular veins at 0, 1, 2, 4, 6, and 8 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Steiger et al (1999) attributed the initial increase in serum glucose concentrations to enhanced glycogenolysis. The observed hypoglycemia after the initial increase in serum glucose concentrations is a response that appears to occur often in ruminant animals exposed to LPS (Steiger et al, 1999;Waggoner et al, 2009b;Wang et al, 2015). As described by Waggoner et al (2009b), hypoglycemia that follows the initial increase in serum glucose concentrations in LPS-challenged cattle is indicative of glucose utilization exceeding glucose synthesis.…”
Section: Endotoxin Challengementioning
confidence: 91%
“…Steiger et al (1999) attributed the initial increase in serum glucose concentrations to enhanced glycogenolysis. The observed hypoglycemia after the initial increase in serum glucose concentrations is a response that appears to occur often in ruminant animals exposed to LPS (Steiger et al, 1999;Waggoner et al, 2009b;Wang et al, 2015). As described by Waggoner et al (2009b), hypoglycemia that follows the initial increase in serum glucose concentrations in LPS-challenged cattle is indicative of glucose utilization exceeding glucose synthesis.…”
Section: Endotoxin Challengementioning
confidence: 91%
“…These results differ slightly from the observations of others that have used much higher doses of LPS to suppress gluconeogenesis and showed increases in glycolytic genes such as Phosphofructokinase-1 and decreases in gluconeogenesis genes Fructose 2, 6 bisphosphate, Phosphoenolpyruvate carboxy kinase, and Glucose 6 phosphate. [21, 22, 42, 43]. Our studies showed decreases in glycolytic and gluconeogenic genes with no change in Pepck .…”
Section: Discussionmentioning
confidence: 55%
“…ACSS3 plays a role in the activation of acetate to specific metabolic fate, and has also a high activity to activate propionate [ 11 ]. In mitochondria, ACSS3 catalyzes the conversion of propionate to propionyl-CoA at the first step of the propionate-originated gluconeogenesis pathway [ 12 ]. In this study, steers exhibited higher (p = 0.06) ACSS3 mRNA levels than did bulls ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%